Helena Edgren: Mercy and Justice. Miracles of the Virgin Mary in Finnish Medieval Wall-Paintings. (Finska Fornminnesföreningens Tidskrift, 100). (1993). 235 s. - Munk-Jørgensen, Wivan (Historie/Jyske Samlinger, 1996)
-